Are Men More Polite Than Women? Deconstruct the Politeness Strategy in Disagreement Statements - Putri, Fitrari Ramadhani Salsabila; Firmonasari, Aprillia (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
This research aims to find out the politeness strategies used by the participants for stating the disagreement and to disclose the stereotypes about women being more polite than men or not. The data source for this research was obtained from the disagreement statements performed by female and male participants in one of the Vice Debates’ episodes entitled Parents, Teachers & Students Debate the US Education System. The qualitative method was used to describe the differences in politeness strategies performed by women and men participants. This research found 37 politeness strategies used by all participants. Men participants produced 24 disagreement statements which contained 3 types of politeness strategies, which are bald-on record, positive politeness, and negative politeness. Positive politeness became the highest strategy used by men participants, it convinced the stereotype that men do not use an emotional approach when responding to the interlocutor is not necessarily true. On the contrary, female participants only delivered 13 disagreement statements but used all of the politeness strategies, which are bald-on record, positive politeness, negative politeness, and off-record. Negative politeness became the highest type and it reassures women do not always use long-winded talk when stating the disagreement.